Investigating identities (Rodopi, 2009)
Preliminary Material – INVESTIGATING IDENTITIES /Marieke Krajenbrink and Kate M. Quinn – NATIONALITY INTERNATIONAL: DETECTIVE FICTION IN THE LATE TWENTIETH CENTURY /Eva Erdmann – ARTICULATING AND DISARTICULATING CULTURE AND IDENTITY IN VÁZQUEZMONTALBÁN’S SERIE CARVALHO /Stewart King – POPULAR GENRE AND THE POLITICS OF THE PERIPHERY: CATALAN CRIME FICTION BY WOMEN /Anne M. White and Shelley Godsland – QUESTIONS OF IDENTITY: AN EXPLORATION OF SPANISH DETECTIVE FICTION /Anne L. Walsh – ABYSS OF THE SENSES: LES RIVIÈRES POURPRES BY JEAN-CHRISTOPHE GRANGÉ /Sjef Houppermans – FRACTURED IDENTITIES: JEAN-CLAUDE IZZO’S TOTAL KHÉOPS /Agnès Maillot – DETECTING ETHNICITY: JAKOB ARJOUNI AND THE CASE OF THE MISSING GERMAN DETECTIVE NOVEL /Arlene A. Teraoka – DOUBLE IDENTITY: HARD-BOILED DETECTIVE FICTION AND THE DIVIDED “I” /John Scaggs – PLUM’S THE GIRL! JANET EVANOVICH AND THE EMPOWERMENT OF MS COMMON AMERICA /Theo D’Haen – MURDER AND LOVE: RUSSIAN WOMEN DETECTIVE WRITERS /Willem G. Weststeijn – PERSPECTIVES ON THE DETECTIVE NOVEL IN AFRIKAANS /Hans Ester – WANTED: NATIONAL ALGERIAN IDENTITY /Beate Burtscher-Bechter – “TROUBLING” THRILLERS: POLITICS AND POPULAR FICTION IN NORTHERN IRELAND LITERATURE /Marisol Morales Ladrón – DOUBLE DUTCH: IMAGE AND IDENTITY IN DUTCH AND FLEMISH CRIME FICTION /Sabine Vanacker – CULTURAL IDENTITY IN SWISS GERMAN DETECTIVE FICTION /Christopher Jones – UNRESOLVED IDENTITIES IN ROTH AND RABINOVICI: REWORKING THE CRIME GENRE IN AUSTRIAN LITERATURE /Marieke Krajenbrink – CRIME NOVELS IN ITALY /Costantino C. M. Maeder – THE DETECTIVE AND THE DISAPPEARED: MEMORY, FORGETTING AND OTHER CONFUSIONS IN JUAN JOSÉ SAER’S LA PESQUISA /Philip Swanson – CASES OF IDENTITY CONCEALED AND REVEALED IN CHILEAN DETECTIVE FICTION /Kate M. Quinn – FROM A GOOD FIRM KNOT TO A MESS OF LOOSE ENDS: IDENTITY AND SOLUTION IN MARTIN AMIS’ NIGHT TRAIN /Brian Duffy – NOTES ON CONTRIBUTORS – INDEX. Investigating Identities: Questions of Identity in Contemporary International Crime Fiction is one of the relatively few books to date which adopts a comparative approach to the study of the genre. This collection of twenty essays by international scholars, examining crime fiction production from over a dozen countries, confirms that a comparative approach can both shed light on processes of adaptation and appropriation of the genre within specific national, regional or local contexts, and also uncover similarities between the works of authors from very different areas. Contributors explore discourse concerning national and historical memory, language, race, ethnicity, culture and gender, and examine how identity is affirmed and challenged in the crime genre today. They reveal a growing tendency towards hybridization and postmodern experimentation, and increasing engagement with philosophical enquiry into the epistemological dimensions of investigation. Throughout, the notion of stable identities is subject to scrutiny. While each essay in itself is a valuable addition to existing criticism on the genre, all the chapters mutually inform and complement each other in fascinating and often unexpected ways. This volume makes an important contribution to the growing field of crime fiction studies and to ongoing debates on questions of identity. It will therefore be of special interest to students and scholars of the crime genre, identity studies and comparative literature. It will also appeal to all who enjoy reading contemporary crime fiction
10.1163/9789042029170
Keywords: Detective and mystery stories; Identity (Psychology) in literature; Identity (Philosophical concept) in literature; Criticism; interpretation; etc